Smoking is associated with hypermethylation of the APC 1A promoter in colorectal cancer: the ColoCare Study. Issue 3 (29th September 2017) - Barrow, Timothy M; Klett, Hagen; Toth, Reka; Böhm, Jürgen; Gigic, Biljana; Habermann, Nina; Scherer, Dominique; Schrotz‐King, Petra; Skender, Stephanie; Abbenhardt‐Martin, Clare; Zielske, Lin; Schneider, Martin; et al.
Abstract: Smoking tobacco is a known risk factor for the development of colorectal cancer and for mortality associated with the disease. Smoking has been reported to be associated with changes in DNA methylation in blood and in lung tumour tissues, although there has been scant investigation of how epigenetic factors may be implicated in the increased risk of developing colorectal cancer. To identify epigenetic changes associated with smoking behaviours, we performed epigenome‐wide analysis of DNA methylation in colorectal tumours from 36 never‐smokers, 47 former smokers, and 13 active smokers, and in adjacent mucosa from 49 never‐smokers, 64 former smokers, and 18 active smokers. Our analyses identified 15 CpG sites within the APC 1A promoter that were significantly hypermethylated and 14 CpG loci within the NFATC1 gene body that were significantly hypomethylated ( p LIS < 1 × 10 −5 ) in the tumours of active smokers. The APC 1A promoter was hypermethylated in 7 of 36 tumours from never‐smokers (19%), 12 of 47 tumours from former smokers (26%), and 8 of 13 tumours from active smokers (62%). Promoter hypermethylation was positively associated with duration of smoking (Spearman rank correlation, ρ = 0.26, p = 0.03) and was confined to tumours, with hypermethylation never being observed in adjacent mucosa. Further analysis of adjacent mucosa revealed significant hypomethylation of four loci associated with the TNXB gene in tissue from active smokers. Our findings provide exploratory evidence for hypermethylation of the key tumour suppressor gene APC being implicated in smoking‐associated colorectal carcinogenesis. Further work is required to establish the validity of our observations in independent cohorts. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.